Distorsión e insatisfacción de la imagen corporal en una universidad de Cartagena (2015)
This investigation project aims to describe the characteristics of the distortion and dissatisfaction of the corporal image at a university in Cartagena. Having as reference that the corporal image includes two components: one perceptul that refers to the estimation of the size and the appearance, while another refers to an attitudinal that reflects the feelings and attitudes towards itself body, Gardner (1996). Therefore when talking about distorted body image misperception focus on the dimensions and other physical characteristics of the body itself. The assessment of the itself body image is subjective and very often does not match with reality (Behar, Vargas & Cabrera, 2011). Therefore the term «body dissatisfaction» is used to denote the set of emotions, thoughts and negative attitudes toward physical appearance. Dissatisfaction can be caused by perceptual distortion, the discrepancy between perceived and ideal body or simply because discontent with the own body (Order, 2003). The study was a quantitative approach based on non-experimental descriptive with a crosssectional design. The population who where chose were VI semester university students of psychology, a sample of 83 students was taken, 54 female and 29 male. As an average age of 20.8 years was obtained, given that the age recorded was 18 and the maximum was 25 years.